Potential climate change favored expansion of a range limited species, Haematostaphis barteri Hook f. - Moutouama, Jacob Koundouonon; Fandohan, Belarmain Adandé; Biaou, Honoré Samadori Sorotori; Amahowe, Ogoundjè Isidore; Moutouama, Fidèle Tchossi; Natta, Armand K. (Journal of Agriculture and Environment for International Development (JAEID), 2016)
Understanding impact of climate change on range breadth of rare species can improve the ability to anticipate their decline or expension and take appropriate conservation measures. Haematatostaphis barteri is an agroforestry species of the Sudanian centre of endemism in Africa. We investigeted impact of climate change on range of suitable habitats for this species in Benin,using the Maximum Entropy algorithm under R software. Five environmental variables were used with the regional climate model under the new Representation Concentration Pathways (RCP). Moisture Index of the Moist Quarter and Slope variability had the greatest predictive importance for the range of suitable habitats for H. barteri. Its Potential breadth was found to be currently limited to the Atacora Mountain Chain (AMC) and covers 0.51% of national territory. Climate change was projected to favor expansion of suitable habitats for H. barteri by 0.12% and 0.05%, respectively for the RCP4.5 and RCP8.5. These habitats were however mostly out of the local protected areas network. Climate change would extend range of habitats for H. barteri. Observed protection gaps suggest need for integrating this species into formal in situ, on-farm or ex situ conservation schemes.